Intimate Partner Violence among Canadian Muslim Women - Alghamdi, Maryam S. (Journal of interpersonal violence, 2022)
An examination of the interaction of pre- and post-migration stressors is critical to understanding Canadian Muslim immigrant women?s experience of intimate partner violence (IPV). This study uses a dominant qualitative design, supplemented by quantitative data to understand eight Canadian Muslim immigrant women?s experience of IPV from six countries of origin. Five themes were identified: (a) childhood exposure to trauma and violence, (b) iron cage of society, (c) the fusion of love and violence, (d) post-migration challenges and assistance, and (e) toll and consequences of IPV. These themes are described to illustrate the trajectory in the development of IPV and the participants? eventual decision to leave their relationship. Pre-migration experiences included adverse childhood experiences, family history of IPV, and difficulty with help-seeking for IPV. Post-migration challenges of language difficulties, lack of social connections, internalized familial patriarchal values, and sexism influenced women?s help-seeking and decision-making. Results from this sample suggested that immigrant Muslim women are likely more affected by IPV in comparison to Canadian-born Muslim women, experienced more stressors, less support, delayed help-seeking process, and more serious mental health consequences. Quantitative measures revealed negative effects of IPV on women?s mental and overall health. The roles of ethnic communities, religious institutions, law enforcement, and service providers in supporting Canadian Muslim women with experience of IPV are discussed.